Water deprivation-induced hypoxia and oxidative stress physiology responses in respiratory organs of the Indian stinging fish in near coastal zones - Samar Gourav Pati; Falguni Panda; Abhipsa Bal; Biswaranjan Paital; Dipak Kumar Sahoo (PeerJ, 2024)
Background Water deprivation-induced hypoxia stress (WDIHS) has been extensively investigated in numerous fish species due to their adaptation with accessory respiratory organs to respire air but this has not been studied in Indian stinging fish Heteropneustes fossilis. Data regarding WDIHS-induced metabolism in accessory respiratory organ (ARO) and gills and its relationship with oxidative stress (OS) in respiratory organs of air-breathing fish H. fossilis, are limited. So, this study aimed to investigate the effects of WDIHS (0, 3, 6, 12, and 18 h) on hydrogen peroxide (H2O2) as reactive oxygen species (ROS), OS, redox regulatory enzymes, and electron transport enzymes (ETC) in ARO and gills of H. fossilis. Methods Fish were exposed to air for different hours (up to 18 h) against an appropriate control, and ARO and gills were sampled. The levels of oxygen saturation in the body of the fish were assessed at various intervals during exposure to air. Protein carbonylation (PC) and thiobarbituric acid reactive substances (TBARS) were used as OS markers, H2O2 as ROS marker, and various enzymatic activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), along with the assessment of complex enzymes (I, II, III, and V) as well as the levels of ascorbic acid (AA) and the reduced glutathione (GSH) were quantified in both the tissues. Results Discriminant function analyses indicate a clear separation of the variables as a function of the studied parameters. The gills exhibited higher levels of GSH and H2O2 compared to ARO, while ARO showed elevated levels of PC, TBARS, AA, SOD, CAT, and GPx activities compared to the gills. The activities of GR and ETC enzymes exhibited similar levels in both the respiratory organs, namely the gills, and ARO. These organs experienced OS due to increased H2O2, TBARS, and PC levels, as observed during WDIHS. Under WDIHS conditions, the activity/level of CAT, GPx, GR, and GSH decreased in ARO, while SOD activity, along with GR, GSH, and AA levels decreased in gills. However, the activity/level of SOD and AA in ARO and CAT in gills was elevated under WDIHS. Complex II exhibited a positive correlation with WDIHS, while the other ETC enzymes (complex I, III, and V) activities had negative correlations with the WDIHS. Discussion The finding suggests that ARO is more susceptible to OS than gills under WDIHS. Despite both organs employ distinct redox regulatory systems to counteract this stress, their effectiveness is hampered by the inadequacy of small redox regulatory molecules and the compromised activity of the ETC, impeding their ability to effectively alleviate the stress induced by the water-deprivation condition.